Pengaruh Modal Dan Biaya Produksi Terhadap Laba Bersih Pada Usaha Mikro Kecil Menengah Sektor Makanan Dan Minuman Di Kabupaten Sidoarjo - Hibatin Wafiroh; Abdul Hamid; Rika Yuliastuti (PUTRA JAWA PUBLISHER, 2025)
Understanding and analyzing the partial and simultaneous effects of capital and production expenses on net profit in small and medium-sized businesses in the food and beverage industry in Sidoarjo Regency is the aim of this study. The study uses a quantitative approach. The micro, small, and medium-sized businesses (MSMEs) that are active in Sidoarjo Regency make up the study's population. Using purposive selection approaches, a sample of 100 MSME operators in the food and beverage industry was chosen. Through the distribution of questionnaires, primary data was gathered for this study. Multiple Linear Regression is the data analysis technique used in this study, and SPSS software was used for processing. The results of this study show that, when taken into account jointly, capital and production costs have a major impact on the net profit of MSMEs in the food and beverage industry in Sidoarjo Regency.